2006
DOI: 10.1007/s11103-005-4921-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Snowy Cotyledon 1 Mutant of Arabidopsis Thaliana: The Impact of Chloroplast Elongation Factor G on Chloroplast Development and Plant Vitality

Abstract: During seedling development chloroplast formation marks the transition from heterotrophic to autotrophic growth. The development and activity of chloroplasts may differ in cotyledons that initially serve as a storage organ and true leaves whose primary function is photosynthesis. A genetic screen was used for the identification of genes that affect selectively chloroplast function in cotyledons of Arabidopsis thaliana. Several mutants exhibiting pale cotyledons and green true leaves were isolated and dubbed sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
113
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(125 citation statements)
references
References 25 publications
11
113
0
1
Order By: Relevance
“…Once this block is broken, by the addition of either Glc or Suc to the growth medium, cotyledons unfold and true leaves are formed. These CLP alleles do not have white cotyledons, as observed for a subset of plastid mutants, the locus white cotyledon1 (Yamamoto et al, 2000), the cyo1 stromal elongation factor G (SCO1; Albrecht et al, 2006;Ruppel and Hangarter, 2007), or the thylakoid protein disulfide isomerase CYO1/SCO2 (Shimada et al, 2007;Albrecht et al, 2008;Tanz et al, 2012; for review, see Pogson and Albrecht, 2011). These sco mutants are not affected in chloroplast development during embryogenesis in the developing silique.…”
Section: The Search For Substratesmentioning
confidence: 90%
“…Once this block is broken, by the addition of either Glc or Suc to the growth medium, cotyledons unfold and true leaves are formed. These CLP alleles do not have white cotyledons, as observed for a subset of plastid mutants, the locus white cotyledon1 (Yamamoto et al, 2000), the cyo1 stromal elongation factor G (SCO1; Albrecht et al, 2006;Ruppel and Hangarter, 2007), or the thylakoid protein disulfide isomerase CYO1/SCO2 (Shimada et al, 2007;Albrecht et al, 2008;Tanz et al, 2012; for review, see Pogson and Albrecht, 2011). These sco mutants are not affected in chloroplast development during embryogenesis in the developing silique.…”
Section: The Search For Substratesmentioning
confidence: 90%
“…Whereas the VAR genes encode FtsH proteases associated with thylakoid protein degradation, Miura et al found that FUG1 encodes chloroplast prokaryotic translation initiation factor2, suggesting that it functions in chloroplast protein synthesis. A loss-of-function mutation of SCO1, which encodes chloroplast elongation factor G (Albrecht et al, 2006), was also found to suppress var1 and var2 phenotypes (see figure). Additional experiments showed that fug1 and sco1 mutants are deficient in translation of chloroplast proteins, such as D1.…”
Section: It's All About Balancementioning
confidence: 96%
“…Mutants with pigment deficiencies that are confined either to cotyledons or true leaves also suggest differences in the regulation of plastid development in these two organs. Arabidopsis thaliana plants with mutations in VAR1 and VAR2 (FtsH proteases) have normal green cotyledons (Sakamoto et al, 2003), whereas a number of other Arabidopsis mutants, including wco (unidentified gene product) (Yamamoto et al, 2000), sco1 (chloroplast elongation factor G) (Albrecht et al, 2006), and sig2 and sig6 (sigma factors) (Privat et al, 2003;Ishizaki et al, 2005), have albino or pale-green cotyledons but normal green leaves. Despite these reports, how cotyledonspecific chloroplasts develop remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%